ANALISIS PENGARUH FUND CASH FLOW, FUND SIZE, FUND LONGEVITY, EXPENSE RATIO DAN TURNOVER RATIO TERHADAP KINERJA REKSA DANA (Studi Kasus : Reksa Dana Pendapatan Tetap Periode Tahun 2011-2015) - Sukmaningrum, Galuh; Mahfud, M. Kholiq (Diponegoro Journal of Management, 2016)
Mutual funds are used to collect funds from public investor to be invested in portfolio securities by investment manager who has license from OJK. The purpose of this study is to examine the influence of fund cash flow, fund size, fund longevity, expense ratio and turnover ratio to performance of fixed income mutual funds. The data used are SBI, JCI, TNA annually, NAB monthly, fund age, and prospectus annually. The samples used in this study were 20 fixed income mutual funds which listed and published by OJK during period 2011-2015. The Analytical method used in this study is pooled panel LSDV (Least Square Dummy Variable) with F-statistic test, t-statistic test, determination of coefficients (R2), classical assumption test such as autocorrelation test, heteroscedasticity test and multicolinearity test. The results of this study indicate that fund longevity has a positive significant on performance of mutual funds and expense ratio has a negative significant on performance of mutual funds, while fund cash flow, fund size dan turnover ratio have insignificant effect on performance of mutual funds.